FABRICATION OF MULTI-WALLED CARBON NANOTUBE (MWCNT) TRANSPARENT AND FLEXIBLE CONDUCTIVE FILMS ON POLYETHYLENE TEREPHTHALATE (PET) SUBSTRATES - PURNOMO - NIM: 23716304, IKHSAN
Transparent conducting film (TCF) is a critical component in many optoelectronic devices. Recent studies have shown that carbon nanotubes (CNT) provide good chemical, optoelectronic, and flexible properties in its films, making them as a substituent of the last used materials. In this study we evaluated fabrication and optoelectronic performance of transparent conductive films based on multi-walled carbon nanotube (MWCNT) on PET. PET alkali treated using NaOH with 1, 2 and 3 M and alkalization time 30, 45, 60 dan 75 minutes. MWCNT acid treated AT by HNO3 68%, 8 hours, 120oC. MWCNT ink dispersed in carboxymethyl cellulose (CMC), sodium dodecyl benzene sulfonate (SDBS) and gum arabic (GA) solution using probe-sonicator for 2, 5, 8 and 11 minutes. MWCNT was dispersed in three differet concentrations, 0.1, 0.2 and 0.3 wt.%. MWCNT ink was coated onto polyethylene terephthalate (PET) substrates using spin-coater at 1000 rpm (50 s). Then, TCFs washed by aquades for TCF GA and HNO3 8 M for TCF CMC and dried in 70oC for 30 minutes. The parameters optimization had been monitored by UVÃ‚Â–Vis spectroscopy and transmission electron microscope (TEM). Sheet resistance (Rs) and optical transmittance (T) of TCF-MWCNT were investigated using four point probe method and UV-Vis spectroscopy, respectively. Scanning electron microscope was also used to characterize the surface morphology of TCF. Bending experiments to measure a change in the electrical resistance were also performed manually. This study shows that optoelectronic properties of MWCNT films were highly dependent on the MWCNT concentrations. The best performance was obtained from the ink with MWCNT acid treated concentration of 0.3 wt.% with corresponds to Rs ~22 k/sq and T ~73% (at 550 nm). TCF-MWCNT also presented excellent electrical stability after 100 bend cycles. There was not significantly change in the electrical resistance for TCF-MWCNT suggest that TCF-MWCNT have a great potential for flexible electronic devices.